Special Issue: Human Movement Monitoring Using Wearable Sensor Technology - Yi-Chung Lin (Sensors, 2025)
The accurate and reliable measurement of human movement stands as a cornerstone in the evaluation of athletic performance, the management of fall risk, the prevention of injury, and the guidance of clinical rehabilitation [...]